Дифузійні процеси в зоні контакту міді з молібденом - Захаров, С.М.; Цях, Р.; Ганієв, Т.Р.; Храновська, К.М.; Харченко, Г.К. (Видавничий дім "Академперіодика" НАН України, 2008)
Diffusion processes in the contact zone of Cu with Mo on their diffusion joining through the ultradisperse layer of Cu are investigated by the method of radioactive isotopes. It is established that the parameters of diffusion of an isotope 63Ni in the contact zone of Cu with Mo essentially depend on the preliminary treatment of samples by argon ions. An asymmetry of the concentration profiles of the distribution of 63Ni in Cu and Mo is observed. A depth of penetration of 63Ni into Cu is greater as compared with that into Mo for all processing modes.